A Comparison of Islamic and Conventional Unit Trust Funds' Performance in Malaysia - Azrul Haffiz, Mohamed (2010)
The growths of demand for Islamic products lead to a growth of unit trust, or funds, based on Islamic principles. The main aim of this research is to observe the differences in performance between Islamic and conventional funds in the context of Malaysian capital market. This study uses 94 funds as the sample, which is made up of 44 Islamic funds and 50 conventional funds. To achieve the major objectives of this paper, Sharpe ratio, Treynor index and Jensen alpha are used to evaluate the mutual funds performance. To examine whether the differences in performance are influenced by the choice of market benchmarks, this study uses both KLCI and EMAS indexes. This study finds that, the differences between Islamic funds and conventional funds are not significant based on t-tests and the locations of both type of funds according to Mann-Whitney tests. The use of either KLCI Index or EMAS as a market benchmark does not influence the result.